Innovative processing route combining fused deposition modelling and laser writing for the manufacturing of multifunctional polyamide/carbon fiber composites. (August 2020) - Lupone, Federico; Padovano, Elisa; Veca, Antonino; Franceschetti, Lorena; Badini, Claudio
Abstract: An innovative manufacturing method, based on Fused Deposition Modelling (FDM) and Laser Writing (LW) technologies, was developed to integrate electrically conductive tracks within high strength 3D printed parts. Carbon fibers reinforced polyamide composites were processed by FDM according to three different printing architectures by varying the raster angle in the layer sequence. Laser writing was then performed to obtain conductive tracks on the surface of the printed parts. The process-structure-property relationship of components before and after the writing of conductive tracks was investigated. The tensile behaviour and the track resistance of samples were correlated to the direction of filament extrusion within the layers, and consequently to fibers orientation. Tracks showing good aesthetic quality and the lowest electrical resistance were obtained on samples with [±45] architecture. These tracks displayed the lowest electrical resistance ever reached by laser writing on metal-free polymer composites (0.008 kΩ/cm). Samples with [±45] architecture also showed high strength (72.9 MPa) and stiffness (7.7 GPa). The integration of FDM and LW emerges as a new approach to transform the surface of high strength polymer composites parts into a highly valuable system. These multifunctional components can find applications in several industrial fields such as automotive, aeronautics, and appliances. Graphical abstract: Unlabelled Image Highlights: An innovative manufacturing route combining fused deposition modelling and laser writing was successfully developed. Laser writing was performed on FDM samples to obtain "in situ" conductive tracks on their surface. Tensile properties and track resistance of FDM specimens were correlated to the fiber orientation inside the layers. The lowest electrical resistance values ever reached by laser writing on metal free polymer composites were obtained.